Addressing human capital development in public agriculture extension in Southern Africa: Assessing Mozambique’s experience - Gêmo, Hélder; Davis, Kristin E. (International Food Policy Research Institute, 2015)
The purpose of this study is to review the human capital development (HCD) challenges in agricultural extension in the southern Africa region, focusing on Mozambique as a country case study. Reviewing HCD in extension is critical because enhancing and maintaining adequate human capital, both in terms of quantity and competence, have been often challenging tasks. Mozambique was selected as a case study because the country has been experiencing particular challenges in public extension HCD due to policy and administrative bureaucratic issues. This is in spite of the acknowledgment by government and key stakeholders of the critical role for extension in contributing to agricultural growth. The study focuses on public extension since it is present in many of the 15 countries of the region. It focuses particularly on services provided (or not provided) to smallholder farmers.